2021
DOI: 10.3390/ma15010201
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Magnetic Properties of Intermetallic Rare-Earth-Transition-Metal Compounds: A Review

Abstract: This review discusses the properties of candidate compounds for semi-hard and hard magnetic applications. Their general formula is R1−sT5+2s with R = rare earth, T = transition metal and 0≤s≤0.5 and among them, the focus will be on the ThMn12- and Th2Zn17-type structures. Not only will the influence of the structure on the magnetic properties be shown, but also the influence of various R and T elements on the intrinsic magnetic properties will be discussed (R = Y, Pr, Nd, Sm, Gd, … and T = Fe, Co, Si, Al, Ga, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 118 publications
2
7
0
Order By: Relevance
“…The obtained results showed that the distribution of iron is quite equal in all fraction but microspheres, which include high-magnetic iron minerals associated with intermeta lics, are mainly concentrated in the magnetic fractions obtained at current values of 2, and 4 A (0.25, 0.345, and 0.422 Tesla, respectively). It can be supposed that iron in th compounds has different valence forms and different magnetic properties [44]. At th same time, particles containing low-magnetic iron and aluminum were not found in th separated magnetic fractions.…”
Section: Resultsmentioning
confidence: 99%
“…The obtained results showed that the distribution of iron is quite equal in all fraction but microspheres, which include high-magnetic iron minerals associated with intermeta lics, are mainly concentrated in the magnetic fractions obtained at current values of 2, and 4 A (0.25, 0.345, and 0.422 Tesla, respectively). It can be supposed that iron in th compounds has different valence forms and different magnetic properties [44]. At th same time, particles containing low-magnetic iron and aluminum were not found in th separated magnetic fractions.…”
Section: Resultsmentioning
confidence: 99%
“…An important aspect characterizing the ferromagnetic materials is the Curie temperature, which varies drastically between classes of materials or even for materials within the same class, depending on the microscopic ingredients giving rise to the ferromagnetic ground state. Intermetallic compounds based on transition metals have a larger Curie temperature, while those based only on rare-earth have smaller ordering temperatures [ 70 , 71 , 72 , 73 , 74 ]. CePdSb itself has a small Curie temperature compared with the requirements for practical applications, but it has one of the largest ordering temperatures of its class.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the low-field response was improved by simply adjusting the Fe concentration using conventional metallurgical approach [21]. In addition, as a similar approach for improvement of an Fe-rare earth permanent magnets [28,29], an increase in the neighboring Fe-Fe distance by interstitial hydrogen absorption stabilizes the FM state, realizing a transition at temperatures higher than room temperature [30,31]. Meanwhile, the proposed compound system has a shortcoming of the splitting phenomenon, which is correlated with the diffusion of hydrogens [24,25,[32][33][34].…”
Section: Introductionmentioning
confidence: 99%